2004
DOI: 10.1038/nsmb851
|View full text |Cite
|
Sign up to set email alerts
|

Regulated nucleosome mobility and the histone code

Abstract: Post-translational modifications of the histone tails are correlated with distinct chromatin states that regulate access to DNA. Recent proteomic analyses have revealed several new modifications in the globular nucleosome core, many of which lie at the histone-DNA interface. We interpret these modifications in light of previously published data and propose a new and testable model for how cells implement the histone code by modulating nucleosome dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
300
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(310 citation statements)
references
References 73 publications
7
300
0
3
Order By: Relevance
“…nucleosome positioning may be one mechanism by which RelB promotes transcription silencing and tolerance. Although it is well established that the overall stability of nucleosome depends on its constituent DNA sequence and histone modifications (18,50), how such stability takes place is not clearly understood (51). Our striking finding that H3K9me2 modification always associated with stable nucleosomes, either in a basal/silent position (R0) or in a repressive position (T0 and T1), whereas H3K4me3 associated with permissive/open positions, suggests that histone methylation may play a role in nucleosome positioning.…”
Section: Discussionmentioning
confidence: 85%
“…nucleosome positioning may be one mechanism by which RelB promotes transcription silencing and tolerance. Although it is well established that the overall stability of nucleosome depends on its constituent DNA sequence and histone modifications (18,50), how such stability takes place is not clearly understood (51). Our striking finding that H3K9me2 modification always associated with stable nucleosomes, either in a basal/silent position (R0) or in a repressive position (T0 and T1), whereas H3K4me3 associated with permissive/open positions, suggests that histone methylation may play a role in nucleosome positioning.…”
Section: Discussionmentioning
confidence: 85%
“…While most of the PTMs with known in vivo roles are located in the N-terminal tails, mounting evidence suggests that PTMs of core histones are as important (73,74), particularly to regulation of DNA accessibility (75). A large number of core histone PTMs are known to exist (76), investigation of their functional roles is an active area of research (74).…”
Section: Enhanced Accessibility To Ptm Sitesmentioning
confidence: 99%
“…9,10 However, K120 is also acetylated in bulk histones preparations. 11 It is intuitive to assume that these PTMs are mutually exclusive; however, genome-wide analysis suggested that H2BK120ac is part of a "signature" of 17 histone PTMs that mark core promoters of active genes. 12 The well established notion that core promoters are nucleosome-free is at odds with the finding of most of these PTMs in histones positioned in such areas, a fact that could be rationalized by the relative imprecision of sonicated chromatinbased assays.…”
Section: Introductionmentioning
confidence: 99%